Complete sequence of mitochondrial DNA of Gloiopeltis furcata (Postels and Ruprecht) J. Agardh - Kei Watanabe; Takahiro Kishimoto; Yuya Kumagai; Takeshi Shimizu; Toshiki Uji; Hajime Yasui; Hideki Kishimura (Mitochondrial DNA. Part B. Resources, 2019)
Although most red algae produce agar and carrageenan, Gloiopeltis furcata produces funoran as polysaccharide component. In this study, the complete G. furcata mitochondrial genome was determined. It had a circular mapping molecular with the length of 25,636 bp and contained 49 genes including 24 protein-coding, two rRNA, and 23 tRNA. Phylogenetic analysis showed that G. furcata was separated with the other polysaccharide-producing red algae. This is the first report of complete mitochondrial genome from funoran producing red algae.